The Implementation Of The Character Education In History Teaching - Zahro, Mustika; Sumardi, Sumardi; Marjono, Marjono (JURNAL HISTORICA, 2017)
A Character education is the efforts made by the school to shape, steer and build behavior students in accordance with values are to certain norms. The Character is needed to reduce students in anticipation of future challenges which is expected to be more weight and complex. The Teaching history in high school have a big responsibility to form the character of students. The problems of this research are, the base of character education at school, the implementation of character education in teaching history, and the value of character developed by teaching history. The purpose of this research, to know the base of character education at school, the implementation of character education in teaching history, and the value of a character developed by teaching history. The subject of the research is three history teacher some students. The kind of this is descriptive with a qualitative approach. The results of the value character education in history teaching is patriotic, honest, diciplined, communicative and religius. This research is expected to be a contribution to the reader literature. Keywords: the character education, history teaching